Predictive Factors of Failure of Conservative Reduction of Intussusception in Children - علي وجيه; العباس باسل; عيسى كميت (Latakia University Journal -Medical Sciences Series, 2021)
Objective: The aim of this study is to determine the factors that influence the failure of conservative (hydrostatic) reduction of intussusception in children. Methods: A retrospective study of patients with ileocolic intussusception presented to our institute between 2015 and 2020, in which demographic, clinical, radiological, and laboratory data of patients were reviewed. Results: Data were collected from 106 patients, 7 of whom were excluded, and underwent primary surgery as a contraindication for hydrostatic reduction, and the study sample included 99 children. The success rate of Hydrostatic Reduction was 60.6%, with the recurring cases considered a failure to reduction. The effect of 15 variables on the success of the Hydrostatic Reduction was studied through statistically univariable analysis, and it was found that both weight, age, duration of symptoms and length of the compound were significantly greater in the failure group, and an important correlation was found between the failure of the reduction and both the left position of the compound head Intussusception, presence of free fluid within the peritoneum, presence of gaseous fluid levels, negative Doppler signal, bloody defecation, vomiting, and abdominal distension. While no significant relationship was observed for sex, laboratory criteria or mesenteric lymph node enlargement with the outcome of the reduction. Using multivariate analysis, 4 independent risk factors were identified for reduction failure: bloody defecation, duration of symptoms, compound length and free fluid presence within the peritoneum. Conclusion: These criteria can be adopted in the patients’ high-risk assessment of failure of a Hydrostatic Reduction for further investigations or to predict the potential need for surgical intervention.